Book Review: Handbook of curriculum evaluation. edited by arieh lewy. new york: longman, inc., 1977. 306pp: - Davis, Harold S (NASSP Bulletin, 1978)
Keywords: book.review; dept.edu

Preparing principals for action, leadership - Davis, Harold S (NASSP Bulletin, 1974)
Both the curricula and methodology of preparing principals is the subject of this article. Describing procedures that work, it will interest principals as well as professors of school administration. © 1974, Sage Publications. All rights reserved.
Keywords: dept.edu

Book Review: Supervision: the reluctant profession by ralph l. mosher and david e. purpel. boston: houghton mifflin co., 1972. 206 pp. 4.95 - Davis, Harold S (The Educational Forum, 1973)
Keywords: book.review; dept.edu

Book Review: Principles of skill acquisition edited by e. a. bilodeau with the assistance of ina McD. bilodeau. new york: academic press, inc., 1969. 353 pp. 5.95 - Davis, Harold S (The Educational Forum, 1971)
Keywords: book.review; dept.edu

Book Review: Education and manpower: theoretical models and empirical applications by tore thonstad. edinburgh: oliver & boyd ltd., 1968. 155 pp. 9.25 - Davis, Harold S (The Educational Forum, 1970)
Keywords: book.review; dept.edu

Book Review: A new system of education by b. everard blanchard, homewood, il.: ETC publications, 1975. 154 pp. 8.95 - Davis, Harold S. (The Educational Forum, 1976)
Keywords: book.review; dept.edu

Educational Technology: Instructional Programming and Didakometry by Ake Bjerstedt. New York: Wiley-Interscience, 1972. 300 pp. $9.50. - Davis, Harold S. (Educational Forum, 1974)
Keywords: dept.edu; ⛔ No DOI found

Review of Phi Delta Kappa Fastbacks (Numbers 21-32) - Davis, Harold S (Educational Forum, 1973)
Keywords: dept.edu

Teaching-Learning - Davis, Harold S. (The Educational Forum, 1971)
Ways of Teaching by Ronald T. Hyman. Philadelphia: J. B. Lippincott Company, 1970. 283 pp. $3.95
Keywords: dept.edu